2018
DOI: 10.30845/ijll.v5n4p6
|View full text |Cite
|
Sign up to set email alerts
|

The Blended Learning Approach and Its Application in Language Teaching

Abstract: The purpose of this paper is to conduct a meta-analysis of the pedagogical practice of blended learning, or the use of both direct instruction and online learning in second language instruction. A thorough review of the relevant literature over the last two decades on blended learning generally, and second language instruction using blended learning techniques in particular, is presented. Demonstrating the positive benefits from applying blended learning in language instruction, the study results should help g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 22 publications
2
16
0
1
Order By: Relevance
“…The results agree with the previous research conducted by Banditvilai (2016) and Tawil (2018) that proved the effectiveness of using the blended learning mode in the ESP training as it enhanced learners' performance, cognitive ability, learning motivation, and learning styles. The experiment provides a new insight into ESP course management whose delivery might be based on the CRM system, which could maintain a teacher-student contact and provide automated guidance to a student throughout the course.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results agree with the previous research conducted by Banditvilai (2016) and Tawil (2018) that proved the effectiveness of using the blended learning mode in the ESP training as it enhanced learners' performance, cognitive ability, learning motivation, and learning styles. The experiment provides a new insight into ESP course management whose delivery might be based on the CRM system, which could maintain a teacher-student contact and provide automated guidance to a student throughout the course.…”
Section: Discussionsupporting
confidence: 91%
“…Blended learning mode and its impact on learners' performance, cognitive ability, learning motivation, and learning styles Literature review on the use of blended learning mode in the ESP training found that there is the relation between the mode and learners' performance, cognitive ability, learning motivation, and learning styles (Banditvilai, 2016;Bielousova, 2017;Radosavlevikj, 2015;Whyte & Sarré, 2017;Tawil, 2018;Tuomainen, 2016). For example, Radosavlevikj (2015) found that 80% of the surveyed students showed greater motivation in taking the online courses than in the in-classroombased ones.…”
Section: Student-tailored System and Its Impact On Learners' Learning Styles Cognitive Skills And Learning Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers also highlighted online features used in blended learning and related them to students' views (Sari & Wahyudin, 2019;Al Zumor, Al Refaai, Bader Eddin, & Aziz Al-Rahman, 2013). Most studies have shown positive effect of blended learning on English achievement (Vymetalkova & Milkova, 2019;Qindah, 2018;Ghazizadeh & Fatemipour, 201;Banditvilai, 2016;Liu, 2013;Vasbieva, Klimova, Agibalova, Karzhanova, & Bírová, 2016;Tawil, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Además de otorgar un rol más importante a la oralidad, este programa propone enfocarse en las clases sincrónicas, de manera que estas sean un espacio para la práctica de los contenidos gramaticales y la resolución de dudas. Para conseguir este objetivo, se considera establecer una tendencia gradual hacia clases invertidas o sistema blended, cuya eficiencia para la enseñanza de segundas lenguas se ha venido demostrando ampliamente en el aprendizaje en línea (Hamilton, 2018;Plesec Gasparic;2017;Tawil, 2018). Desde el inicio, el alumnado trabaja de manera autónoma en el Aula Virtual (Moodle) y revisa los contenidos lingüísticos más significativos; así, las clases son un espacio no solo para la retroalimentación por parte del cuerpo docente, sino también para resolver dudas, reforzar, compartir y, cuando el grupo lo permite, experimentar.…”
Section: Introductionunclassified